Comparison of nasopharyngeal samples for SARS‐CoV‐2 detection in a paediatric cohort. (19th February 2021) - Rodrigues, Jorge; Gouveia, Catarina; Santos, Madalena Almeida; Costa, Olga; Côrte‐Real, Rita; Brito, Maria João
Abstract : Aim: The diagnosis of coronavirus disease 2019 (COVID‐19) depends on accurate and rapid testing. Choosing an appropriate sample may impact diagnosis. Naso‐oropharyngeal swabs (NOS) are most frequently used, despite several limitations. Since studies suggest nasopharyngeal aspirate (NPA) as a superior alternative in children, we hypothesised collecting both nasopharyngeal swab and aspirate would improve our diagnostic accuracy. Methods: Observational, longitudinal, prospective study from 7 March to 7 May in a tertiary paediatric hospital in Lisbon. The objective was to compare the rate of detection of SARS‐CoV‐2 between NOS and NPA samples collected simultaneously. Results: A total of 438 samples collected from 85 patients with confirmed COVID‐19. There were 47.7% overall positive specimens – 32% (70/219) positive NOS and 63.5% (139/219) positive NPA. The tests were 67.6% concordant ( k  = 0.45). 50.3% had positive NPA with negative NOS, while 1.3% had positive NOS with negative NPA. NPA proved to be more sensitive (98.6% with 95% confidence interval 91.2–99.9% vs. 49.6% with 95% confidence interval 41.1–58.2%, P  < 0.001). Additionally, the difference between NPA and NOS positive samples was statistically significant across all population groups (age, health condition, clinical presentation, contact with COVID‐19 patients or need for hospitalisation), meaning NPA is more sensitive overall. Conclusions: Nasopharyngeal aspirates had greater sensitivity than naso‐oropharyngeal swabs in detecting SARS‐CoV‐2. Our results suggest paediatric patients would benefit from collecting nasopharyngeal aspirates in hospital settings, whenever feasible, to improve diagnosis of COVID‐19.